Dystocia due to Diplopagus Sternopagus conjoined twins ina buffalo - SREENU, MAKEENA; SRINIVAS, M; NAIDU, K SUBRAMANYAM (The Indian Journal of Animal Reproduction, 2023)
Dystocia due to Diplopagus Sternopagus conjoined twins was relieved by caesarean section in a 9-year-old third lactation Murrah buffalo.